Configuration correlation governs slow dynamics of supercooled metallic liquids - Hu, Yuan-Chao (2020)
The origin of dramatic slowing down of dynamics in metallic glass-forming liquids toward their glass transition temperatures is a fundamental but unresolved issue. Through extensive molecular dynamics simulations, here we show that, contrary to the previous beliefs, it is not local geometrical orderings extracted from instantaneous configurations but the intrinsic correlation between configurations that captures the structural origin governing slow dynamics. More significantly, it is demonstrated by scaling analyses that it is the correlation length extracted from configuration correlation rather than dynamic correlation lengths that is the key to determine the drastic slowdown of supercooled metallic liquids. The key role of the configuration correlation established here sheds important light on the structural origin of the mysterious glass transition and provides an essential piece of the puzzle for the development of a universal theoretical understanding of glass transition in glasses.